Revisão sobre o uso de adições minerais em concretos sustentáveis - Teodoro, Laura Helena (Universidade Federal de São Carlos, 2022)
The civil engineering sector, despite being necessary for human comfort and development, is one of the biggest contributors to the perish of these resources. Therefore, it is important to implement techniques to promote better environmental conditions and achieve sustainable construction. Within the theme of sustainability in civil construction, recycling and reuse of materials as substitutes for cement or aggregates plays a major role in reducing CO2 emissions and, consequently, in making concrete more sustainable. Therefore, the present work, of bibliographic scope, seeks to evaluate the current techniques for the reuse of materials, using them as raw material for another product. In civil construction and other areas, there is a lot of waste that is wasted and can be reused, being the solution to avoid the extraction of natural products. Some additional cementitious materials, incorporated replacement levels, as well as the effect of these additions on the compressive strength of concrete were evaluated, highlighting the importance of recycling and reuse of waste in civil construction. For this evaluation, a database was created with compressive strength results available in the literature. These data were used in comparative analyzes that took as reference the results corresponding to the additions of fly ash, rice husk ash, glass powder and blast furnace slag. It was not possible to reach a definitive conclusion because there was a great variation in the results of compressive strength of concrete for all materials, only the glass powder that did not show an increase in strength at 7 and 28 days for the analyzed data, fly ash showed increases up to 20% replacement, rice husk ash showed improvement up to 25% replacement, and blast furnace slag had the best results for 100% replacement.
Review on the use of mineral additions in sustainable concrete
Keywords: Sustentabilidade; Concreto; Adilções minerais; Sustainability; Concrete; Mineral additions; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL